Basics of biomedical ultrasound for engineers - Azhari, Haim, 1955- (Hoboken, N.J. : Wiley : IEEE, 2010)
'Basics of Biomedical Ultrasound for Engineers is a structured textbook for university engineering courses in biomedical ultrasound and for researchers in the field. This book offers a tool for building a solid understanding of biomedical ultrasound, and leads the novice through the field in a step-by-step manner. The book begins with the most basic definitions of waves, proceeds to ultrasounds in fluids, and then delves into solid ultrasounds, the most complicated kind of ultrasound. It encompasses a wide range of topics within biomedical ultrasound, from conceptual definitions of waves to the intricacies of focusing devices, transducers, and acoustic fields'--Provided by publisher
Includes bibliographical references and index
Keywords: Ultrasonics in medicine; Ultrasonics; Ultrasonography -- methods; Ultrasonic Therapy